2007
DOI: 10.1002/app.26677
|View full text |Cite
|
Sign up to set email alerts
|

Effect of zinc oxide on the viscosity, tack, and peel strength of ENR 25‐based pressure‐sensitive adhesives

Abstract: Viscosity, loop tack, and peel strength of epoxidized natural rubber (ENR 25 grade)-based pressure-sensitive adhesive was studied in the presence of zinc oxide. The zinc oxide concentration was varied from 10-50 parts per hundred parts of rubber (phr). Coumarone-indene resin with loading from 20 to 100 phr was chosen as the tackifier resin. Toluene was used as the solvent throughout the experiment. The adhesive was coated on the substrate using a SHEEN hand coater to give a coating thickness of 60 mm. Viscosit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
37
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 45 publications
(39 citation statements)
references
References 12 publications
2
37
0
Order By: Relevance
“…Also, a gradual drop of shear strength with increasing tackifier loading is also observed. Recently, we have carried out a study on the effect of zinc oxide on the viscosity, tack and peel strength of ENR 25-based pressure-sensitive adhesives [7]. It is shown that viscosity and loop tack of adhesive increases with increasing zinc oxide concentration.…”
Section: Introductionmentioning
confidence: 99%
“…Also, a gradual drop of shear strength with increasing tackifier loading is also observed. Recently, we have carried out a study on the effect of zinc oxide on the viscosity, tack and peel strength of ENR 25-based pressure-sensitive adhesives [7]. It is shown that viscosity and loop tack of adhesive increases with increasing zinc oxide concentration.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, we have carried out several investigations on the viscosity, tack, peel and shear strength of natural rubber (NR) and epoxidized natural rubber (ENR) [1][2][3][4][5]. It has been shown that the viscosity and tack of natural rubber-based adhesive increases with resin content due to the concentration effect of tackifier resin.…”
Section: Introductionmentioning
confidence: 99%
“…It is obvious from the graph that viscosity of adhesive increases with an increase in zinc oxide concentration, and the rate of increase is faster as the filler content is increased. This observation is attributed to the thickening effect of the zinc oxide, which acts as the filler in the adhesive formulation [8]. This finding suggests that greater interaction between the filler and adhesive system occurs.…”
Section: Viscositymentioning
confidence: 93%